El Fuego Nuevo: interpretación de una « ofrenda contada » tlapaneca (Guerrero, México) - Danièle Dehouve (Journal de la Société des Américanistes)
New Fire: Interpretation of a numerical offering by the Tlapanecs (Guerrero, Mexico). The first description of Tlapanec numerical offerings dates from 1930 and Karl Nowotny showed the relation between them and some images belonging to the Borgia Group codex. However, since that date, the interpretations have not progressed notably. This article presents the first results of an ongoing research in various communities of a Tlapanec municipality. It compares an offering to Fire performed in two villages, in order to bring to light, beyond surface variations, its three level structure and the native conception of sacred symbolical numbers.